A Framework of Concurrent Mechanism Based on Java Multithread - Wuxue Jiang; Qi Li; Zhiming Wang; Jianfeng Luo (Institute of Advanced Engineering and Science, 2013)
The continuously increased demand for paralleling multitask in domains such as grid computing and cloud computing has significantly promoted research on concurrent mechanism and concurrent programming. The Java programming language supports multithread mechanism for developing paralleling programs, however, it is difficult to apply Java concurrent primitives to specific problems. Thus, for the development of high reliable and qualitative Java concurrent programs, this paper analyses Java multithread mechanism and it’s realization, studies the concurrent mechanism based on Java synchronization and interactive communication mechanism , compares the concurrent structure based on operating system and based on Java multithread, sums up some concurrent programming rules and strategies to prevent deadlock. A frame instance based on entire synchronization is presented, which can help to develop concurrent programs quickly. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3296